High secretion of interferons by human plasmacytoid dendritic cells upon recognition of Middle East respiratory syndrome coronavirus - Scheuplein, Vivian A; Seifried, Janna; Malczyk, Anna H; Miller, Lilija; Höcker, Lena; Vergara-Alert, Júlia; Dolnik, Olga; Zielecki, Florian; Becker, Björn; Spreitzer, Ingo; König, Renate; Becker, Stephan; et al. (Journal of virology, 2015)
The Middle East respiratory syndrome coronavirus (MERS-CoV) emerged in 2012 as the causative agent of a severe respiratory disease with a fatality rate of approximately 30%. The high virulence and mortality rate prompted us to analyze aspects of MERS-CoV pathogenesis, especially its interaction with innate immune cells such as antigen-presenting cells (APCs). Particularly, we analyzed secretion of type I and type III interferons (IFNs) by APCs, i.e., B cells, macrophages, monocyte-derived/myeloid dendritic cells (MDDCs/mDCs), and by plasmacytoid dendritic cells (pDCs) of human and murine origin after inoculation with MERS-CoV. Production of large amounts of type I and III IFNs was induced exclusively in human pDCs, which were significantly higher than IFN induction by severe acute respiratory syndrome (SARS)-CoV. Of note, IFNs were secreted in the absence of productive replication. However, receptor binding, endosomal uptake, and probably signaling via Toll-like receptor 7 (TLR7) were critical for sensing of MERS-CoV by pDCs. Furthermore, active transcription of MERS-CoV N RNA and subsequent N protein expression were evident in infected pDCs, indicating abortive infection. Taken together, our results point toward dipeptidyl peptidase 4 (DPP4)-dependent endosomal uptake and subsequent infection of human pDCs by MERS-CoV. However, the replication cycle is stopped after early gene expression. In parallel, human pDCs are potent IFN-producing cells upon MERS-CoV infection. Knowledge of such IFN responses supports our understanding of MERS-CoV pathogenesis and is critical for the choice of treatment options. MERS-CoV causes a severe respiratory disease with high fatality rates in human patients. Recently, confirmed human cases have increased dramatically in both number and geographic distribution. Understanding the pathogenesis of this highly pathogenic CoV is crucial for developing successful treatment strategies. This study elucidates the interaction of MERS-CoV with APCs and pDCs, particularly the induction of type I and III IFN secretion. Human pDCs are the immune cell population sensing MERS-CoV but secrete significantly larger amounts of IFNs, especially IFN-α, than in response to SARS-CoV. A model for molecular virus-host interactions is presented outlining IFN induction in pDCs. The massive IFN secretion upon contact suggests a critical role of this mechanism for the high degree of immune activation observed during MERS-CoV infection.